Pediatric Pulmonary Function Testing in COVID-19 Pandemic and Beyond. A Position Statement From the Hellenic Pediatric Respiratory Society - Fouzas, Sotirios; Gidaris, Dimos; Karantaglis, Nikolaos; Opsimos, Harry; Alexopoulos, Emmanouil I.; Douros, Konstantinos; Kirvassilis, Fotios; Paraskakis, Emmanouil; Anthracopoulos, Michael B.; Marangos, Markos; Tsanakas, Ioannis; , the Hellenic Pediatric Respiratory Society (Frontiers in Pediatrics, 2021)
As the COVID-19 pandemic is still evolving, guidelines on pulmonary function testing that may dynamically adapt to sudden epidemiologic changes are required. This paper presents the recommendations of the Hellenic Paediatric Respiratory Society (HPRS) on pulmonary function testing in children and adolescents during the COVID-19 era. Following an extensive review of the relevant literature, we recommend that pulmonary function tests should be carried out after careful evaluation of the epidemiologic load, structured clinical screening of all candidates, and application of special protective measures to minimize the risk of viral cross infection. These principles have been integrated into a dynamic action plan that may readily adapt to the phase of the pandemic.